Arthroscopic Debridement of the Posterior Compartment of the Knee after Total Knee Arthroplasty - Tsuyoshi Ohishi; Tomotada Fujita; Daisuke Suzuki; Kazufumi Yamamoto; Hiroki Ushirozako; Yukihiro Matsuyama (Case Reports in Orthopedics)
Arthroscopic debridement of the posterior compartment of the knee after total knee arthroplasty is difficult because it is tough to obtain intercondylar notch views. Herein, we performed arthroscopic debridement of the posterior compartment of an infected knee after total knee arthroplasty by using a transseptal portal in a 62-year-old woman with rheumatoid arthritis. Palpation of anatomical landmarks and posterior capsule protection are important for safe creation of a transseptal portal following to making 2 posterior portals.